Non Neutralizing Antibodies to Tissue Type Plasminogen Activator in the Serum of Acute Myocardial Infarction Patients Treated with the Recombinant Protein - Cugno, Massimo; Cicardi, Marco; Colucci, Mario; Bisiani, Giuliana; Angelica Merlini, Piera; Spinola, Alessandra; Paonessa, Raffaella; Agostoni, Angelo (Thrombosis and Haemostasis, 1996)
Recombinant tissue-type plasminogen activator (rt-PA) is currently used as a thrombolytic agent in the management of acute myocardial infarction (AMI). Since it is known that other recombinant proteins induce antibody formation when administered to humans, we determined the presence of anti-rt-PA antibodies in serial blood samples from 60 AMI patients (43 treated with and 17 without rt-PA). Blood samples were taken upon hospital admission, 15 days and 1, 3,6 months thereafter. A blood sample was also collected from 200 healthy subjects. Using an ELISA, anti-rt-PA antibodies were detected as serum immunoglobulins specifically binding immobilized rt-PA. AMI patients before treatment and normal subjects exhibited negligible levels of anti-rt-PA antibodies; both groups had only one outlier value. Fifteen days after rt-PA treatment, 2 AMI patients showed an increase in antibody titer beyond the highest normal value. This titer progressively decreased during the following 6 months. The antibodies from these two patients bound rt-PA both in a solid and fluid phase. They bound melanoma t-PA to a lower degree and did not bind urokinase type plasminogen activator at all, indicating specificity for t-PA. The marked temporal relationship between rt-PA infusion and antibody appearance indicated that antibody formation had been elicited by the infusion of rt-PA. Nevertheless, the lack of anti-rt-PA antibody interference with rt-PA function in vitro, along with the favourable clinical outcome of those patients having such antibodies would indicate that the appearance of anti-rt-PA antibodies does not interfere with the physiological fibrinolytic activity.